Research on the Pattern Evolution of Innovation Output Space in Guangzhou Metropolitan Area Based on Authorized Invention Patent Data - Shan Zhuoran; Liu Sisi; Yuan Man; Zhu Junqing (Redai dili)
As areas with high population and economic concentration, metropolitan areas are important geographical units for innovation transformation and radiation. However, studies on innovation space have mainly focused on the entire country, urban agglomerations, provinces, and cities, with less attention paid to metropolitan areas as important scales of scientific and technological innovation. In addition, existing studies often emphasize the overall characteristics of the innovation output space, neglecting diverse innovation subjects such as enterprises, scientific research institutions, and individuals. Based on the data of authorized invention patents in the Guangzhou metropolitan area, this study applied spatial research methods, such as spatial autocorrelation, kernel density analysis, and buffer analysis, to explore the overall evolution pattern of innovation output space in the metropolitan area as well as the evolution characteristics and influencing factors of the three types of innovation outputs, namely enterprises, scientific research institutions, and individuals, to provide a scientific basis for the development of innovation space and the optimization of innovation resources. The results show that: (1) the evolution of innovation output space generally follows the pattern of "gathering in the core area of the main district of the central city in a metropolitan region, generating innovation output growth points in the secondary cities and forming a number of innovation output cross-border integration areas." (2) The innovation output space of enterprises continues to cluster toward industrial parks and technology parks with clear boundaries, and the extensive construction of parks has driven the decentralized development of innovation output space of enterprises; The innovation output space of scientific research institutions, with strong stability, has always been highly concentrated in the core area of the main city of Guangzhou and has expanded with the construction of university towns within the metropolitan area; The individual innovation output has shifted from "explosive spatial dispersion" to "organized spatial convergence", and the adsorption effect of urban rail transit on individual innovation output is becoming increasingly significant. (3) The three types of innovation outputs always have spatial proximity characteristics, and enterprise innovation is the main driving force for innovation diffusion in the periphery of metropolitan areas. (4) Regional innovation output is influenced by both the innovation environment and innovation inputs, among which government support is the most critical driving force affecting the three types of innovation outputs. Economic base and location conditions are important pillars for the three types of innovation outputs, while the degree of openness has a greater contribution to enterprise innovation output by facilitating technological spillovers and knowledge flows. In general, the overall spatial evolution of innovation output in the metropolitan area follows the development pattern of "single core-expansion-multicore," with the spatial evolution of the three types of innovation outputs being closely related to the construction of regional industry-university-research centers and major transportation facilities.